Enhancing EFL Learners’ Writing Skill via Journal Writing - Hanif Maulaniam Sholah (Alsuna: Journal of Arabic and English Language, 2019)
English writing, for a number of EFL learners, appears to be challenging. Let alone, this language should be mastered by every learner since English is mean of communication between nation and nation, country and country all over the world. This paper aims to investigate whether learners can improve their writing ability and grow out of the writing difficulties by engaging in journal writing activity. 60 second-year students from the two writing classes are involved. One treated as the experimental group (EG) and the other as the control group (CG), at the Faculty of English Department Education of the IAI Al-Qolam Gondanglegi were invited to participate in the study, whose findings shows the benefits of journal writing as an extensive activity to enhance learners' writing motivation and foster their writing skill as well as to build a close interactive communication between teachers and learners.